El control interno y su incidencia en los niveles de riesgo del departamento de operaciones de la compañía Agrolaya S.A., cantón Quevedo, período 2012.. - Cedeño Saavedra, Karla Vanessa (2015)
This research is based on the Internal Control and its impact on risk levels operations department of the company Agrolaya SA, Canton Quevedo. Period 2012. For the execution of this work has raised the following formulation of the problem What is the impact of the Internal Control in the risk levels of the department of operations of the Company Agrolaya SA, Canton Quevedo, Period 2012? The same is justified because it allows the recognition of their competitive weaknesses, establishing potential risks to which the administration faces, looking to meet, assess, establish and correct flaws in it, using techniques or tools Audit of Internal Control that contribute to decision making and adoption of appropriate criteria that will transform them into opportunities. In addition we note that the methodology used for this study was the interview and questionnaire tools used to develop the different independent variables, so the results yielded the research were……